Demonstration of impaired neurovascular coupling responses in TG2576 mouse model of Alzheimer's disease using functional laser speckle contrast imaging - Tarantini Stefano; Fülöp Gábor Áron; Kiss Tamás; Farkas Eszter; Zölei-Szénási Dániel; Galvan Veronica; Tóth Péter József; Csiszar Anna; Ungvári Zoltán István; Yabluchanskiy Andrij (2017)
Increasing evidence from epidemiological, clinical, and experimental studies indicates that cerebromicrovascular dysfunction and microcirculatory damage play critical roles in the pathogenesis of many types of dementia in the elderly, including both vascular cognitive impairment (VCI) and Alzheimer's disease. Vascular contributions to cognitive impairment and dementia (VCID) include impairment of neurovascular coupling responses/functional hyperemia ("neurovascular uncoupling"). Due to the growing interest in understanding and pharmacologically targeting pathophysiological mechanisms of VCID, there is an increasing need for sensitive, easy-to-establish methods to assess neurovascular coupling responses. Laser speckle contrast imaging (LSCI) is a technique that allows rapid and minimally invasive visualization of changes in regional cerebromicrovascular blood perfusion. This type of imaging technique combines high resolution and speed to provide great spatiotemporal accuracy to measure moment-to-moment changes in cerebral blood flow induced by neuronal activation. Here, we provide detailed protocols for the successful measurement in neurovascular coupling responses in anesthetized mice equipped with a thinned-skull cranial window using LSCI. This method can be used to evaluate the effects of anti-aging or anti-AD treatments on cerebromicrovascular health.